Optimization of Cobalt Chrome 3D re-entrant Auxetics fabricated using Selective Laser Melting. (1st March 2023) - Singh, Daljeet; Tobin, Daniel; Dowling, Luke; Trimble, Daniel
Highlights: A geometric model of the repeated unit cell based 3D Auxetic metamaterial has been developed. The re-entrant Auxetic samples have been fabricated using CoCr powder by the 3D printing process of Selective Laser Melting. The effect of geometric parameters on the Auxeticity of the CoCr re-entrant model has been evaluated in a concurrent way. The optimal values of the parameters for maximum Auxeticity have been obtained by using the suggested approach. Abstract: An approach to study the effect of geometric parameters on the Poisson's ratio of a three-dimensional re-entrant Cobalt Chrome Auxetic structure has been presented. The Auxetic mechanical structure has been realized with the help of Additive Manufacturing. The mechanical properties and Poisson's ratio of the physical samples were determined using compression testing and Digital Image Correlation (DIC). A Finite Element model is used to estimate the Poisson's ratio numerically. A Design of Experiments (DOE) and Finite Element Analysis (FEA) based optimization study is further performed in order to investigate the effects of the different geometric parameters on the Poisson's ratio of the Auxetic samples. The DOE model is used to determine the values of the parameters for an optimal performance of the samples in terms of the observed Auxetic behaviour.